Não-cumulatividade no ICMS - Jorge, Plínio Augusto Lemos (2009)
The object of this work is the study of the non-cumulativeness principle in the ICMS concept. In this way, it aims to accomplish this study under the parameter of Constitutional supremacy, taking under consideration the hierarchy of the rules of positive law. The quality of principle assigned to the non-cumulativeness is a recurring theme at work, before the necessity of situating above other rules of Brazilian positive law to demonstrate, in a clear way, the necessity of its observance. Therefore, we will study the Brazilian constitutional system and the competence in creation of tributes in the course of the work, following the study about the general constitutional as well as the taxation principles. It approaches the ICMS characteristics using the incidence of taxation origin of this income and from then on, it leads to the non-cumulativeness principle study, its origin, concepts and its relation to the Complementary Law. Finally, it sets up the study of the principle under the established exceptions in the Federal Constitution and the created exceptions made by the infra-constitutional legislator. Due to the amplitude of the theme, a few epistemological cuts will be made. However, no dissolution of the continuity of the work object was implied. On the contrary, there was an effort to deepen the work theme so as to demonstrate the peculiarities of the non-cumulativeness in the Brazilian legal ordinance. Anyway, the conclusion aimed claims the close importance of the non-cumulativeness principle as a unique route to the correct incidence of the ICMS